Dominant SCN2A Mutation Causes Familial Episodic Ataxia and Impairment of Speech Development - Fazeli, Walid; Becker, Kerstin; Herkenrath, Peter; Düchting, Christoph; Körber, Friederike; Landgraf, Pablo; Nürnberg, Peter; Altmüller, Janine; Thiele, Holger; Koy, Anne; Liebau, Max C.; Simon, Thorsten; Dötsch, Jörg; Cirak, Sebahattin (Neuropediatrics, 2018)
Mutations in SCN2A are associated with a heterogeneous clinical spectrum including epilepsy and autism. Here, we have identified a peculiar phenotype associated with vaccination related exacerbations of ataxia. We report the first family with three individuals affected by SCN2A-associated episodic ataxia (EA) with impaired speech development. The index patient manifested his first episode of subacute cerebellar ataxia at the age of 12 months, 3 weeks after vaccinations for measles, mumps, rubella, and varicella. Cranial magnetic resonance imaging showed a lesion of the left cerebellar hemisphere, which was first considered as a potential cause of the ataxia. The patient fully recovered within 3 weeks, but developed three very similar episodes of transient ataxia within the following 24 months. Whole exome sequencing of the index patient revealed a heterozygous autosomal-dominant mutation in SCN2A (NM_021007, c.4949T > C; p.L1650P), which was confirmed in the likewise affected mother, and was then also identified in the younger brother who developed the first episode of ataxia. We hereby extend the recently described spectrum of SCN2A-associated neurologic disorders, emphasizing that SCN2A mutations should also be considered in familial cases of EA. Coincidental imaging findings or other associated events such as immunizations should not protract genetic investigations.
Keywords: ataxia; exome sequencing; ion channel; NaV1.2; SCN2A; vaccinations